2017
DOI: 10.3748/wjg.v23.i37.6884
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of response to endoscopic treatment in painful chronic pancreatitis

Abstract: AIMTo evaluate the endoscopic treatment efficacy and prognostic factors of long-term response to treatment for painful chronic pancreatitis.METHODSThis retrospective analysis identified 168 patients with painful chronic pancreatitis hospitalized during January 2010-January 2015 in a Romanian tertiary referral center. Data on demographics, medical history, alcohol consumption, smoking habit, clinical parameters, type and number of endoscopic procedures and hospital admissions number were collected from the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
0
6
0
1
Order By: Relevance
“…Furthermore, smoking was found to promote pancreatic calcification (RR 1.44, 95% CI 1.25-1.67; p \ 0.00001) [58][59][60][61][62][63][64] and to increase the risk of developing pancreatic exocrine dysfunction (RR 1.62, 95% CI 1.29-2.04, p \ 0.00001) and diabetes (RR 1.28, 95% CI 1.10-1.48; p = 0.001) in a meta-analysis of seven observational studies of pancreatic calcification (n = 2953), four observational studies of pancreatic exocrine dysfunction (n = 1331), and five observational studies of diabetes (n = 2254) [58][59][60][61][62][63][64][65]. In a meta-analysis of two observational studies, smoking also worsened the long-term prognosis after endoscopic treatment in patients with painful CP (RR 4.73, 95% CI 2.15-10.40; p = 0.0001) [66,67]. In contrast, a meta-analysis of five observational studies showed that smoking cessation had the effect of suppressing the onset of CP (RR 0.58, 95% CI 0.51-0.67; p \ 0.00001) [51][52][53][54][55].…”
Section: Treatmentmentioning
confidence: 99%
“…Furthermore, smoking was found to promote pancreatic calcification (RR 1.44, 95% CI 1.25-1.67; p \ 0.00001) [58][59][60][61][62][63][64] and to increase the risk of developing pancreatic exocrine dysfunction (RR 1.62, 95% CI 1.29-2.04, p \ 0.00001) and diabetes (RR 1.28, 95% CI 1.10-1.48; p = 0.001) in a meta-analysis of seven observational studies of pancreatic calcification (n = 2953), four observational studies of pancreatic exocrine dysfunction (n = 1331), and five observational studies of diabetes (n = 2254) [58][59][60][61][62][63][64][65]. In a meta-analysis of two observational studies, smoking also worsened the long-term prognosis after endoscopic treatment in patients with painful CP (RR 4.73, 95% CI 2.15-10.40; p = 0.0001) [66,67]. In contrast, a meta-analysis of five observational studies showed that smoking cessation had the effect of suppressing the onset of CP (RR 0.58, 95% CI 0.51-0.67; p \ 0.00001) [51][52][53][54][55].…”
Section: Treatmentmentioning
confidence: 99%
“…Other studies with small sample sizes identified smoking, alcohol, incomplete stone removal, lesser narcotic use, pancreas divisum, and MPD stricture as predictive factors of persistent pain using univariate analysis [7,8,10,11,17,18]. Absence of multivariate analysis along with small samples in these studies could not identify independent predictors of persistent pain in patients with chronic calcific pancreatitis.…”
Section: Discussionmentioning
confidence: 77%
“…In the same group, the need for surgery was 14% to 31% in patients with an average follow-up of less than 5 years, whereas it was 0% to 7.5% in those with a minimum average follow-up of 5 years (218,274,277,280,289,291,294). Factors favoring long-term pain response were absence of continuous pain before treatment, absence of daily narcotics use, short disease duration before treatment, absence of PD, absence of pain just before the procedure, no smoking, quitting alcohol, insertion of a 12F stent during treatment, resolution of the stricture after treatment, and improvement in the main duct diameter after treatment (275,277,278,284,285,291,293). Complications such as pancreatitis (6.3%), sphincterotomy bleeding (0.9%), sepsis (0.6%), cholangitis (0.4%), abscess (0.2%), stent migration (3.1%), and changes in the pancreatic duct (0.8%) may be observed during stenting treatment.…”
Section: Question F3-b: How Is Endoscopic Treatment Of Main Pancreatic Duct Stones Performed?mentioning
confidence: 99%